УМУМТАЪЛИМ МАКТАБИ БОШЛАНҒИЧ СИНФЛАРИДА АРТТЕХНОЛОГИЯЛАРНИ ҚЎЛЛАШ ИМКОНИЯТЛАРИ - Куттибекова, Г.Т. (SCIENCE and SOCIETY, 2021)
The article examines the role of using art pedagogy and art therapy technologies in teaching students in fine arts and music lessons in general education.